Peran Perangkat Desa dan Kecamatan terhadap Pengendalian Peningkatan Seks Bebas Melalui Keberadaan Warung Kopi (Studi Kasus di Kabupaten Jember) (The Role of Village and Subdistrict Staff in Controlling The Enhancement of Free Sex Through The Existence o - Renny Arista Ayu Putranti; Mury Ririanty; Iken Nafikadini (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Coffee stall is the places that sell coffee drink and the kind of hot drinks. Coffee stalls also become place where people do effective communication with anyone. But now, some of coffee stalls in Jember regency not only serve taste of coffee, but also use women to get men consumers. The existence of coffe stalls in Jember regency related to the role of local village and subdistrict staffs. The purpose of this researchwas to review the role of village and subdistrict staff in controlling the enhancement of free sex through the existence of coffee stalls. This was qualitative research design with case study method. The result of this research has found that a few of village and subdistrict staffs knew the existence of coffee stalls which have free sex potential. They did sanction based on the existence regional role if there is a violation or local resident’s concern. But, local residents accepted the existence of the coffee stalls because did not disadvantages for them. Activity that they have done to control the existence of coffee stalls which have free sex potential was patrolling. Some times, patrolling has done together with army and police subdistrict. Keywords: Role, Village, Subdistrict Staff, Coffee Stall, Free Sex